LncRNA DCST1-AS1 Promotes Endometrial Cancer Progression by Modulating the MiR-665/HOXB5 and MiR-873-5p/CADM1 Pathways - Wang, Jie; Shi, Pingping; Teng, Huaixiang; Lu, Lixiang; Guo, Hailong; Wang, Xiuqin (Frontiers in Oncology, 2021)
Dysregulation of long noncoding RNA (lncRNA) is implicated in the initiation and progression of various tumors, including endometrial cancer (EC). However, the mechanism of lncRNAs in EC tumorigenesis and progression remains largely unexplored. In this work, we identified a novel lncRNA DC-STAMP domain-containing 1-antisense 1 (DCST1-AS1), which is highly upregulated and correlated with poor survival in EC patients. Overexpression of DCST1-AS1 significantly enhanced EC cell proliferation, colony formation, migration, and invasion in vitro and promoted tumor growth of EC in vivo. Mechanistically, DCST1-AS1 mediated EC progression by inducing the expression of homeobox B5 (HOXB5) and cell adhesion molecule 1 (CADM1), via acting as a competing endogenous RNA for microRNA-665 (miR-665) and microRNA-873-5p (miR-873-5p), respectively. In addition, we found that the expression of miR-665 and miR-873-5p was significantly downregulated, while HOXB5 and CADM1 expression levels were increased in EC tissues. Taken together, our findings support the important role of DCST1-AS1 in EC progression, and DCST1-AS1 may be used as a prognostic biomarker as well as a potential therapeutic target for EC.